Effect of Openings on the Torsional Behavior of SCC Box Beams Under Monotonic and Repeated Loading - Haneen Maad Mahdi; Rafaa M. Abbas (Salehan Institute of Higher Education, 2023)
Repeated Torsional loading occurs in many concrete structures, such as offshore structures, freeways, multistory parking garages, and other structures; however, repeated torsional loading is still poorly understood. This study aims to investigate the effect of openings on the ultimate and cracking torques, angle of twist, and modes of failure of self-compacted R.C. box beams under monotonic and repeated loading. Two groups of eight half-scale box beams with different numbers of circular openings in the web with a diameter of about 30% of the hollow box dimension were investigated. The first group (I) included four beams: one was the control box beam without openings, whereas the rest of the beams were hollow with one, two, or three openings in the web tested under monotonic loading. The second group (II) consisted of the same details as the first one tested under repeated loading. The range of the repeated loading was about 30% and 60% of the ultimate load of the monotonic tests. The study showed that the cracking and ultimate torques and the angle of twist of the tested beams were significantly reduced due to openings in the web. Results revealed a more pronounced effect for monotonic loading, with a maximum reduction of 20% and 26.8% in cracking and ultimate torsional strength, respectively, compared to monotonic loading. Moreover, results revealed that repeated loading causes inelastic deformations in proportion to the number of loading cycles.Â Doi: 10.28991/CEJ-2023-09-09-015 Full Text: PDF